Jurnal Tinjauan : Perbandingan Studi Pendidikan Kewirausahaan di Sekolah Menengah dan Perguruan Tinggi - Ahmad Fahruddin; Dinna Oktavianasari (Student Research Journal, 2025)
Entrepreneurship education prepares young people for workplace competition by equipping them with entrepreneurial skills. This journal compares the mode, curriculum content and impact of entrepreneurship education in high schools and universities. By analyzing various case studies and relevant literature, the research found significant differences in the approach and outcomes of entrepreneurship education at the two levels of education. In secondary schools, more attention is focused on developing attitudes and practical skills. However, in higher education, more emphasis is placed on theory and market analysis. The findings suggest the importance of better integrating the curriculum so that students can have a more well-rounded learning experience.